A New Species of the Genus Boulenophrys (Anura, Megophryidae) from Southern Hunan Province, Central China - Bei Xiao; Jiayan Xi; Shengchao Shi; Hui Li; Leqiang Zhu; Ayinuer Maimaiti; Yalan Xu; Shunhua Liao; Bin Wang; Xiaoyang Mo (Animals)
A new species of Asian horned toad, Boulenophrys, is described from Yongzhou City, Hunan Province, China. The species is a phylogenetically sister to B. yunkaiensis, based on 16S rRNA and COI genes. The new species differs from its congeners, possessing the following combination of characters: (1) moderate body size: SVL 37.6–40.2 mm (38.9 ± 1.3, n = 7) in adult males and SVL 41.8–45.9 mm (43.6 ± 2.1, n = 3) in adult females; (2) tympanum boundary clear: TD/ED 0.48–0.57 in males and 0.47–0.57 in females; (3) the presence of a small horn-like tubercle at the edge of the upper eyelid; (4) vomerine ridge present and vomerine teeth absent; (5) margin of tongue rounded, not notched posteriorly; (6) rough dorsal skin: a discontinuous “V”-shaped ridge with two discontinuous dorsolateral ridges on two sides on the back, dense tubercles on the skin of the ventral surface of the dorsal shank and thigh, and spiny tubercles surrounding the cloaca; (7) slender hindlimbs with heels overlapping when the flexed hindlimbs are held at right angles to the body axis; tibio-tarsal articulation reaching forward between anterior margin of tympanum and posterior corner of eye when leg stretched forward; (8) relative finger length IV < II < I < III, with a subarticular tubercle present at the base of each finger; (9) distinct supernumerary tubercles below the base of I and II toes; (10) toes without lateral fringes and with rudimentary webbing (webbing formula: I1 − 1-II1 − 2-III2 − 3IV3- − 2V).